Pengembangan E-LKM Berbasis Guided Inquiry Learning Berbantuan Liveworksheets pada Materi Hidrokarbon untuk Fase F SMA - Luthfiyah W.R; Alizar (MASALIQ, 2026)
The National Curriculum encourages the use of digital technology to facilitate active, interactive, and student-centered learning. However, hydrocarbon instruction remains dominated by the use of printed worksheets and therefore does not fully support students’ active engagement. This study aims to develop Guided Inquiry Learning-oriented electronic student worksheets (E-LKM) assisted by Liveworksheets for hydrocarbon topics for Phase F senior high school students and to examine the validity of the resulting product. The study employed the Plomp development model, comprising the preliminary research and prototyping phases. The development process was limited to the third prototype stage, which included self-evaluation, expert review, and one-to-one evaluation. Product validation involved three lecturers from the Department of Chemistry, Faculty of Mathematics and Natural Sciences, Universitas Negeri Padang, and two chemistry teachers from SMA Negeri 4 Payakumbuh, while the one-to-one evaluation involved three students with different levels of academic ability. Data were collected through interview guidelines, a needs analysis questionnaire, validation sheets, and a student response questionnaire and were subsequently analyzed using Aiken’s V index and descriptive analysis. The findings showed that the E-LKM obtained an average Aiken’s V value of 0.89, which was categorized as valid. The one-to-one evaluation results also showed that the E-LKM was easy to use, had an attractive visual appearance, and received positive responses from students. Thus, the Guided Inquiry Learning-oriented E-LKM assisted by Liveworksheets for hydrocarbon topics met the validity criteria and demonstrated initial practicality, making it suitable for use as an alternative digital learning medium in chemistry instruction.